Relatório de estágio curricular supervisionado em medicina veterinária - área de clínica de pequenos animais - López, Amanda Silva (2016)
The purpose of this report is to describe the activities carried out and monitored during the Supervised Curricular Internship in Veterinary Medicine, held at the Hospital de Clínicas Veterárias of the Federal University of Rio Grande do Sul (UFRGS), in the area of Small Animal Surgery, under guidance Profo Dro Diego Vilibaldo Beckmann and supervision by Profo Dro João Antônio Tadeu Pigatto. The internship took place from September 1, 2016 to October 31, 2016, totaling 488 hours of practical activities and 90 hours for writing this report. Throughout this work, the place where the internship was performed, activities developed and cases followed, as well as three cases followed, are reported: 1- Intestinal obstruction by foreign body and splenic torsion in a canine, 2 - Total ablation of auditory canal for squamous cell carcinoma in a canine, 3 - Total cystectomy with cutaneous ureterostomy in a canine with transition cell carcinoma.